The influence of cultivation frequency on weed species composition and diversity in flood recession farming in the Okavango Delta, Botswana - Modise Nthaba (Ecological Processes, 2018)
Abstract Introduction Flood recession farming, locally known as molapo farming, is an important livelihood activity for the subsistence farming community around the Okavango Delta. The study was aimed at investigating the influence of cultivation frequency on non-crop species composition. It was carried out in the peripheral settlements of Shorobe, Makalamabedi and Lake Ngami. Methods Vegetation sampling was conducted from March to April 2016 in 36 fields of varying historical cultivation frequencies. The cultivation frequencies were 5, 10 and 15 years with an uncropped control site. Sampling was done in 1-m2 quadrats placed 10 m apart along a line transect. Shannon’s diversity and equitability indices were used to compare diversity for each cultivation frequency within and across the study sites. The Kruskal–Wallis test was used to investigate significant differences in diversity between cultivation frequencies. Rank of abundance was used to determine the association of weeds with the cultivation frequencies. Results Cultivation frequency did not influence species diversity (p > 0.05) at either Lake Ngami or Shorobe. Species evenness was significantly different (p < 0.05) between the cultivation frequencies at Shorobe, but not at either Makalamabedi or Lake Ngami. There was a significant difference (p < 0.05) in diversity indexes across the four cultivation frequencies. The 5-year frequency recorded the highest median score (Md = 1.352) while the 15-year frequency recorded the lowest median score (Md = 1.035). Corchorus tridens was the most abundant non-crop species at the 5- and 15-year frequencies. Cynodon dactylon was most abundant in the 10-year frequency while Cyperus esculentus was most abundant in uncropped fields. Conclusions Cultivation frequency influenced weed species diversity and composition in flood recession farming. Flood recession farming fields were dominated by common weed species which are also troublesome in dryland arable farming. Uncropped sites were composed of wetland species that tolerate some dry periods or seasonal flood plains.